Social media platforms are another form of university violence: A field study on a sample of students at Al-Balqa Applied University - Al rousan, Safwat; Al Rabadi, Wail Minwer; Aljbour, Rami Abed Al Hamid; Almomani, Rana Thani; Mohammed, Hajar Adel Abdelrazeq (Journal of Cultural Analysis and Social Change, 2025)
This study aimed to identify the role of electronic communication platforms in increasing rates of university violence among students of Al-Balqa Applied University. The study adopted the social survey methodology using an electronic questionnaire with a convenience sampling method of (6000) students of the university registered in 2023 in the various colleges of the university. The study results showed that social media platforms (WhatsApp, Facebook, and X) play a role in increasing rates of university violence among students. The overall mean score on the scale was 3.44, with means ranging from 3.35 to 3.55. Facebook ranked first, followed by X, and WhatsApp ranked last, with mean scores of 3.56, 3.48, and 3.33, respectively. This indicates the role of these platforms in increasing rates of university violence among students. The results also showed statistically significant differences in the role of social media (WhatsApp, Facebook, and X) according to the variables of gender, academic achievement (grade), and study type. These differences favored students enrolled in the regular admissions system with acceptable academic achievement, with males scoring higher on the overall score for all three platforms. The study recommended raising awareness among students through families, universities, and the media about the impact of modern technology and communication programs on university youth. It also recommended conducting further studies on the social and psychological effects of these platforms on Jordanian youth.